Cytomegalovirus reactivation and its effect on graft function in post hematopoietic stem cell transplant (HSCT) patients - Sahla Riaz; Nighat Shahbaz; Asghar Ali Kerio; Munazza Nabi Awan; Isra Hidayat; Muhammad Afzal (Medical Journal of South Punjab, 2024)
Objective: To evaluate the effect of Cytomegalovirus reactivation on graft function and to study the factors contributing to primary graft failure in patients underwent hematopoietic stem cell transplant.Methods: We conducted a prospective study at Armed Forces Bone Marrow Transplant center between Jan 2022 to July 2023.This study included 80 patients of all age groups and both genders, suffering from various hematological diseases. Patients with primary graft failure were excluded. CMV reactivation was monitored during two distinct time frames post-transplantation (initial 100 days and day +100 to day +180).Results: Among the study group, 60% of patients experienced CMV reactivation, and 22.5% who received   antiviral treatment developed myelosuppression. CMV reactivation at day +90 had statistically significant correlation(p=0.031) with graft function.18(22.5%) had myelosuppression after CMV treatment with (p value= 0.010). The CD34 dose had a statistically significant correlation with graft function on Day 30 and Day 60. Chimerism analysis at day +60 had significant correlations with CMV reactivation(p=0.042).Conclusion: In conclusion, our study underscores the significance of CMV reactivation as a common complication post-HSCT, with implications for graft function. We observed a substantial myelosuppressive effect associated with antiviral treatment. The study highlights the importance of CD34 dose in graft function assessment. While further research is needed, our findings emphasize the need for vigilant monitoring and tailored interventions to improve outcomes in post-HSCT patients.